Fachsprache - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Aphorismus - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Fachwort - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Gerontolekt - Markewitz, Friedrich (Wörterbücher zur Sprach- und Kommunikationswissenschaft)

Zensur - Markewitz, Friedrich (Diskursmonitor. Glossar zur strategischen Kommunikation in öffentlichen Diskursen)

The Economics of Ideologies - Gries, Thomas; Burs, Carina; Müller, Veronika
Many of the major international and intrastate crises and conflicts, but also the threat to democratic principles, are driven by belief systems and ideologies. They fuel political polarization, which is particularly evident in the battleground of social media. Nevertheless, we hardly pay attention to ideologies, their narratives, functions and organizations in economic theory today. Ideologies as “non-rational beliefs” seem incompatible with rationality in economic models. Therefore, the book examines the role of ideologies and belief systems in individual decision-making behavior from an economic and rational perspective. Due to the fact that people have incomplete information, belief systems and ideologies fulfill a number of important functions. While ideologies themselves serve psychological needs, they are used as a cognitive framework for rational decision-making once they have been adopted through a Bayesian learning process. They influence decisions in a wide range of areas, from consumption and work to politics. This is where the role of ideological organizations becomes important, because they determine the ideological direction of the narratives and their dissemination. Thus, ideologies give a normative direction, for better or for worse. The “quality” of ideological leadership can be evaluated normatively on the basis of principles such as individual sovereignty and human dignity. A democratic discourse requires an information and communication system that enables an evaluation of precisely these ideologies, free from resource and information power.

Decision-Driven Analytics in Smart Factories: Enterprise Architecture Framework for Use Case Specification and Engineering (FUSE) - Weller, Julian; Dumitrescu, Roman (Electronics)
This paper presents a comprehensive design framework for Enterprise Architecture aimed at facilitating decision-driven analytics in smart factories. The motivation behind this research lies in challenges faced by manufacturing companies, such as skilled labor shortages and increasing global competition, alongside the imperative for sustainable production. This journal provides a novel approach for designing and documenting prescriptive analytics use cases in manufacturing environments. The framework addresses the need for effective integration of advanced data analytics and prescriptive analytics solutions within existing production environments, thereby enhancing operational efficiency and decision-making processes. A Design Science Research approach is used to iteratively derive a framework based on stakeholder needs and activities along the prescriptive analytics use case development cycle. The resulting framework is demonstrated and evaluated in an IoT Factory setup in a research facility. From a practical perspective, the framework supports manufacturing companies in systematically designing prescriptive analytics use cases. From a research perspective, it contributes to the body of knowledge on Enterprise Architecture Management (EAM) by operationalizing the design of prescriptive analytics use cases in manufacturing contexts. The main contributions of this study include the development of a framework that supports the planning, design, and integration of prescriptive analytics use cases. This framework fosters interdisciplinary collaboration and aids in managing the complexity of data-driven projects.

Mache dich auf, werde licht! Ein Abriss des weihnachtlichen Ab und Auf anhand des Weihnachtsfilms von Penny 2022 Der Riss / Let's Talk - Schroeter-Wittke, Harald (Weihnachts-Werbespots als moderne Krippenspiele)

Quelleninventare als Forschungsmittel. Zum Potenzial der Netzwerkanalyse in der Repertoireforschung - Plaksin, Anna Viktoria Katrin; Stremel, Sophie (Die Tonkunst)

Trendbericht: Organische Chemie 2025 - Breugst, Martin; Andexer, Jennifer; Barra, Lena; Beil, Sebastian B.; Bierbach, Sascha; Burkhardt, Immo; Dumele, Oliver; Ernst, Martin; Frommer, Jennifer; Gellrich, Urs; Germer, Philipp; Giese, Michael; et al. (Nachrichten aus der Chemie)
Abstract Highlights von November 2023 bis 2024: die erste Einelektron‐C–C‐σ‐Bindung und Anti‐Bredt‐Verbindung; gesättigte Heterocyclen elektrochemisch funktionalisieren; Ausrichten diskotischer Flüssigkristalle; enantioselektive Wagner‐Meerwein‐Umlagerung reiner Aliphaten; photokatalytisch von Furanen zu Pyrrolen; mit Ammoniak zu primären Arylaminen; Metallschrott recyceln mit ionischen Flüssigkeiten; terminale Alkene mit Ni‐Katalysatoren zum (Z)‐ oder (E)‐Alken isomerisieren;neue Fungizide, Medikamente und Alkaloide.

Life Storytelling across Media and Contexts - Mildorf, Jarmila (Narrative Inquiry)

Soundscapes and Storytelling in Literary Interviews: Audionarratological Perspectives - Mildorf, Jarmila (Narrative Inquiry)

Life Storytelling across Media and Contexts (Narrative Inquiry)

60-Gb/s 1:4 Demultiplexer in 22-nm FD-SOI Technology Using TSPC Logic: A Circuit-to-System-Level Analysis and Design - Sadiye, Babak; Iftekhar, Mohammed; Müller, Wolfgang; Scheytt, J. Christoph (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

Synthesis of Amidines Via P(III)/P(V)=O Redox Catalyzed In Situ Formation of Imidoyl Chlorides From Amides - Medvaric, Viktorija; Paradies, Jan; Werner, Thomas (Advanced Synthesis and Catalysis)
Amidines are a ubiquitous class of bioactive compounds found in a wide variety of natural products; thus, efficient strategies for their preparation are in great demand. Herein, a novel protocol is reported for the synthesis of amidines based on P III /P V O redox catalysis. This two‐step, one‐pot approach involves the activation of amides via P III /P V O catalyzed in situ formation of imidoyl chloride intermediates which are directly converted upon reaction with amines into the corresponding amidines. Instead of traditionally used toxic and corrosive chloride sources, hexachloroacetone (HCA) is successfully employed as a halide source. The reaction proceeds with low catalyst loading (2 mol%) in BuOAc as the solvent. Under the optimized conditions, 20 amidines are prepared in yields up to 99%. A feasible mechanism is proposed based on experimental results. The synthetic potential of this method is evaluated in the preparation of the tyrosine kinase inhibitor (TKI) Erlotinib.
Keywords: T2; T; CSSD

Straightforward Access to Terpene-Based 1,2-Diols and Their Acetals as Fragrance Ingredients - Stefanow, Vivian; Kell, Lukas; Leduskrasta, Aiga; Eh, Marcus; Panten, Johannes; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: T4; CSSD

Metal-Free Reduction of Nitrous Oxide via PIII/PV═O Cycling: Mechanistic Insights and Catalytic Performance - Zhou, Rundong; Medvaric, Viktorija; Werner, Thomas; Paradies, Jan (Journal of the American Chemical Society)
Keywords: T2; CSSD

Spatio-spectral diarization of meetings by combining TDOA-based segmentation and speaker embedding-based clustering - Cord-Landwehr, Tobias; Gburrek, Tobias; Deegen, Marc; Haeb-Umbach, Reinhold (Proceedings of INTERSPEECH)
We propose a spatio-spectral, combined model-based and data-driven diarization pipeline consisting of TDOA-based segmentation followed by embedding-based clustering. The proposed system requires neither access to multi-channel training data nor prior knowledge about the number or placement of microphones. It works for both a compact microphone array and distributed microphones, with minor adjustments. Due to its superior handling of overlapping speech during segmentation, the proposed pipeline significantly outperforms the single-channel pyannote approach, both in a scenario with a compact microphone array and in a setup with distributed microphones. Additionally, we show that, unlike fully spatial diarization pipelines, the proposed system can correctly track speakers when they change positions.

Continuous value shaping: A boundary concept for innovating service innovation approaches - Böhmann, Tilo; Roth, Angela; Satzger, Gerhard; Benz, Carina; Beverungen, Daniel; Boes, Andreas; Breidbach, Christoph; Gersch, Martin; Gudergan, Gerhard; Hogreve, Jens; Kurtz, Christian; Langes, Barbara; et al. (Electronic Markets)
Technological advancements and evolving value orientations reshape future value creation and pose new requirements for service innovation. While a variety of disciplines are developing new approaches to drive service innovation, this is primarily done in isolation and generates only fragmented solutions. Sociological theory has proposed “boundary objects” as an effective umbrella for communication and cooperation among communities. Therefore, we introduce continuous value shaping (CVS) as a boundary object describing service innovation approaches along five principles. We reflect on this concept through the different disciplinary lenses of researchers in service marketing, information systems, service engineering, sociology of work, and innovation management. These perspectives highlight how the CVS principles already connect to discourses within the individual disciplines. However, the CVS concept will not only provide an umbrella to embrace existing activities in different academic disciplines. It also assists to identify research themes that will benefit from uniting the power of these disciplines, and it can serve as an integrating framework to conceptualize complex service innovation approaches. Thus, the CVS concept should guide both researchers and practitioners to develop and implement novel innovation and transformation efforts—in and across organizations.
Keywords: Continuous value shaping (CVS); Service research; Service innovation; Digitalization; Sustainability; Interdisciplinary research

Deeper down the rabbit hole - How technology conspiracy beliefs emerge and foster a conspiracy mindset - Trang, Simon Thanh-Nam; Krämer, Tobias; Trenz, Manuel; Weiger, Welt (Information Systems Research (VHB Jourqual 3 A+, FT50))